Do Stakeholders Matter? Nexus of Public Private Partnership Projects for City Street Parking in Uganda - Nduhura, Alex; Nuwagaba, Innocent; molokwane, Thekiso; Muhwezi, Roland (International Journal of Supply Chain Management, 2022)
This study examines the involvement of stakeholders in the use of Public Private Partnership (PPP) Projects for effective urban parking in Kampala City, Uganda. Guiding objectives of the study include (a) to examine the relevance of stakeholder theory to the execution of the management contract PPP project by Kampala Capital City Authority (KCCA) and Multiplex Uganda limited in Kampala (b) to assess stakeholdersâ€™ participation in the execution of management contract PPP project by KCCA and Multiplex limited in Kampala. The study adopted cross-sectional and exploratory study designs. Data was collected using both quantitative and qualitative approaches. The study covered a population of 1335 stakeholders of Kampala City Council and Multiplex limited. A sample size of 297 respondents for quantitative part of the study and 35 respondents for qualitative part of the study. The sample random sampling and purposive sampling technique were applied. Target group included, operational and administrative Staff of KCCA and Multiplex Uganda Limited, Drivers under Uganda Transport Development Agency (UTRADA) as well as Private Car Users.Â Study findings revealed that the stakeholder theory is relevant to the execution of management contract PPP projects. Further to this, participation of key stakeholders in implementing such PPP Projects leads to effective street parking of urban areas and there is a significant relationship between stakeholder participation in the execution of management contract PPP project and ensuring effective street parking in urban areas. The study recommends that KCC must always ensure that Multiplex limited involves all key stakeholders in the execution of the management contract PPP project such as drivers in meetings when discussing about changes being done.Â The changes need to be made for the betterment of work, as stakeholders of Multiplex need to regularly get feedback after meeting. In addition, stakeholders should always be engaged in identifying priority parking spaces.